Exact Solutions and Localized Structures for Higher-Dimensional Burgers Systems - Yan-ze Peng (International Journal of Mathematics and Mathematical Sciences)
A (2+1) dimensional Burgers equation and a coupled higher dimensional Burgers system is studied by the singular manifold method. The Bäcklund transformations are obtained. Some interesting exact solutions are given. Then localized structures, such as dromion and solitoff, are found, and their interaction properties are numerically studied. The fusion phenomena of two dromions, a dromion and a solitoff, are for the first time reported.